0978 Does Increased Risk of Suicide at Night Favor One Method of Suicide Over Another?. (27th April 2018) - Tubbs, A; Perlis, M; Chakravorty, S; Basner, M; Killgore, W; Gehrels, J; Alfonso-Miller, P; Grandner, M
Abstract: Introduction: In a prior investigation, it was shown that the incidence of suicide is higher at night than would be expected. This follow-up analysis evaluates whether the time-of-day-patterning of suicide was different depending on the method/weapon used. Methods: Data for N=33, 813 suicides, including time of fatal injury and method used, were collected from the National Violent Death Reporting System for years 2002–2010. The most common methods included Firearms (N=20, 583), Suffocation (N=6, 670), Poisoning (N=3, 647), Falling (N=939), Sharp Instrument (N=533), Drowning (N=406), Motor Vehicle (N=339), and Fire (N=224). As with the prior analysis, time of fatal injury was categorized into one-hour bins and grouped into four categories: Morning (06:00 to 11:59), Afternoon (12:00 to 17:59), Evening (18:00 to 23:59), and Night (00:00 to 05:59). American Time Use Survey data from the same years estimated of the proportion of the population awake at each hour. This was used to calculate a standardized incidence ratio (SIR), representing the ratio of observed to expected suicides given the proportion of the population likely awake. In the present analysis, each of the four temporal categories were evaluated for differences with respect to method of suicide. Results: Compared to other times of day, nighttime SIRs were statistically significant for drowning (3.72 ± 1.55), falling (4.268 ± 2.234), fire (6.478 ± 3.15), firearms (4.345 ± 1.682), motor vehicle (6.577 ± 3.487), poisoning (4.222 ± 1.749), sharp instrument (3.792 ± 1.463), and suffocation (4.850 ± 1.864). The nighttime SIR for each method did not differ from the total SIR (one-way ANOVA, p=0.54). Conclusion: Suicides occur disproportionately at night, but nighttime wakefulness does not favor one mechanism of suicide over another. This suggests that being awake at night may influence the initial decision to commit suicide, and not the means by which suicide is accomplished. Support (If Any):